A new study on improving the physicochemical and electrochemical properties of SPEEK nanocomposite membranes for medium temperature proton exchange membrane fuel cells using different loading of zirconium oxide nanoparticles. (5th January 2017) - Gashoul, Fatemeh; Parnian, Mohammad Javad; Rowshanzamir, Soosan
Abstract: The present research focused on investigation of physicochemical and electrochemical properties of proton exchange membranes based on sulfonated poly (ether ether ketone) (SPEEK) by using zirconia nanoparticles. Plain and nanocomposite SPEEK membranes with different loadings of microwave-induced gel combustion synthesized ZrO2 were fabricated. Sulfonation of polymer and nanoparticle production was confirmed by H NMR and XRD, respectively. Physical, chemical, and electrochemical properties of membranes were investigated by SEM, IEC, WU, EIS, tensile stress–strain, TGA, Fenton, and hydrolytic stability tests. H NMR spectra represented a DS of 65% for the sulfonated polymer. The prepared nanocomposite membranes possess improved thermal and mechanical stability with higher hydrolytic stability and enhanced oxidative stability. In addition, nanocomposite membranes exhibited higher water uptake with lower IEC. The hygroscopic zirconia nanoparticles resulted higher proton conductivity of nanocomposite membranes at temperatures upper than 80 °C in comparison with pristine SPEEK membrane. All results showed the fabricated nanocomposite membranes have good physicochemical properties and promising future of the introduced approach for PEMFC applications. Highlights: SPEEK/ZrO2 nanocomposite membranes with different loading of nanoparticles were prepared. Physicochemical and electrochemical properties of SPEEK/ZrO2 membranes were investigated. The nanocomposite membranes showed higher thermal, mechanical, and hydrolytic stability. The nanocomposite membranes showed higher proton conductivity at higher temperatures.